Integer optimization applied to the design of robust minimum cost multi-layer networks. - Parodi, Cecilia (2011)
In this work we solve the problem of designing an MPLS data network, to be deployed over an existing SDH/DWDM transport infrastructure, which is itself a combination of technologies. The data and different work hypothesis are from a particular operator: the National Telecommunications Administration (ANTEL) of Uruguay where the problem was originated. The target Data Network is an IP/MPLS Multi-Layer network over which different kinds of services are delivered and therefore with different quality requirements. During the process we will seek to minimize the economical resources incurred by the deployment over the Transport Infrastructure (Transport Network) of ANTEL. The solution found should be of optimal (minimum) cost and must be able to send a known traffic meeting certain quality parameters, even considering simple failures in some section of the Transport Network. The proposed problem is NP-Hard class in terms of computational complexity. Special cases of it are NP-complete problems. We model the problem algebraically as an Integer Mathematical Programming Problem and solve it approximately.